The Influence of Sensory Marketing on Brand-name Coffee Consumption Behavior - Ratsameechot, Boonsom; Intuwonges, Sittiporn; Sukhaparamate, Supawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The objectives of this research were to identify sensory marketing factors that affect brand-name coffee consumption behavior and to examine the overall influence of motivation on brand-name coffee consumption behavior. Conceptual framework of applied research from sensory marketing. Motivation for consumption of brand-name coffee was collected by convenience sampling method among 804 people. Data were analyzed two variables and structural equation modeling. The results were as follows; marketing factors through the five senses of brand-name coffee shops. Five senses affect the distinctiveness of the coffee shop, affecting consumption behavior sense of smell and sound affects the arousal and the taste sensation affects the happiness of the consumer. Including the five sensory factors also affect the motivation for consuming brand-name coffee. Article history: Received 15 March 2023 Revised 14 August 2023 Accepted 18 August 2023 SIMILARITY INDEX = 0.44 %